Cardiac-specific succinate dehydrogenase deficiency in Barth syndrome - Dudek, Jan; Cheng, I-Fen; Chowdhury, Arpita; Wozny, Katharina; Balleininger, Martina; Reinhold, Robert; Grunau, Silke; Callegari, Sylvie; Toischer, Karl; Wanders, Ronald JA; Hasenfuß, Gerd; Brügger, Britta; et al. (EMBO molecular medicine, 2016)
Abstract Barth syndrome (BTHS) is a cardiomyopathy caused by the loss of tafazzin, a mitochondrial acyltransferase involved in the maturation of the glycerophospholipid cardiolipin. It has remained enigmatic as to why a systemic loss of cardiolipin leads to cardiomyopathy. Using a genetic ablation of tafazzin function in the BTHS mouse model, we identified severe structural changes in respiratory chain supercomplexes at a pre-onset stage of the disease. This reorganization of supercomplexes was specific to cardiac tissue and could be recapitulated in cardiomyocytes derived from BTHS patients. Moreover, our analyses demonstrate a cardiac-specific loss of succinate dehydrogenase (SDH), an enzyme linking the respiratory chain with the tricarboxylic acid cycle. As a similar defect of SDH is apparent in patient cell-derived cardiomyocytes, we conclude that these defects represent a molecular basis for the cardiac pathology in Barth syndrome.